The Relevance of Philosophy in Christianity: An Analysis of Philosophy's Contribution to Theological Understanding and Faith Practice - Mesalayuk, Yasrin; Lawalata, Mozes (Theological Journal Kerugma, 2024)
The role of philosophy in Christianity has been a topic of intense discussion since the Patristic era. Philosophy is often viewed as ambiguous in its contributions to theological understanding and the practice of faith. This study aims to analyze the relevance of philosophy in Christianity, particularly as a support for theological reflection and the practical life of Christians. Using a qualitative approach, the research integrates an in-depth literature review of the works of major Christian philosophers such as Augustine, Thomas Aquinas, and Karl Rahner, while also exploring the interaction between philosophy and theology in a contemporary context. The findings reveal that philosophy plays a significant role in three main aspects: (1) providing a rational framework for understanding and communicating theological doctrines, (2) serving as a tool for critical thinking in addressing modern intellectual challenges to faith, and (3) acting as an ethical foundation supporting Christian life practices. These results also indicate that the integration of philosophy with theology enriches the experience of faith and opens constructive interdisciplinary dialogue. In conclusion, philosophy is not only relevant but also essential in strengthening the foundations of Christian theology while advancing a more reflective life of faith. This study makes a significant contribution to the development of interdisciplinary studies between philosophy and theology, offering new insights for church leaders, academics, and Christians in exploring faith rationally and holistically.